2021
DOI: 10.1002/ejic.202100308
|View full text |Cite
|
Sign up to set email alerts
|

New Magnetic and Luminescent Dy(III) and Dy(III)/Y(III) Based Tetranuclear Silsesquioxane Cages

Abstract: We report here the synthesis, structure, luminescence, and magnetic properties of three new cage‐like tetranuclear silsesquioxanes (Et4N)2[(PhSiO1..5)8(Y0.75Dy0.25O1.5)4(O)(NO2.5)6(EtOH)2(MeCN)2] and (Cat)2[(PhSiO1.5)8(DyO1.5)4(O)(NO2.5)6(EtOH)2(MeCN)2] (Cat=Et4N or Ph4P). They present a characteristic green‐yellow emission. The Y3+/Dy3+ compound displays in addition a field‐induced Single Molecule Magnet (SMM) behavior making it the first reported bifunctional magneto‐luminescent silsesquioxane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…Generally, the silsesquioxane ligands are available via in situ hydrolysis and condensation of the key precursor {RSi­(OR′) 3 }. So far, there have been cyclic, acyclic, and polycyclic types of the oligomeric silsesquioxanes with different condensation degrees (i.e., different number of [Si] atoms) being established (e.g., [Si1], , [Si4], [Si5], , [Si6], ,, [Si7], [Si8], [Si9], [Si10], ,, and [Si12]). These various incompletely condensed silsesquioxanes may provide more possibilities to modulate the aggregation of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the silsesquioxane ligands are available via in situ hydrolysis and condensation of the key precursor {RSi­(OR′) 3 }. So far, there have been cyclic, acyclic, and polycyclic types of the oligomeric silsesquioxanes with different condensation degrees (i.e., different number of [Si] atoms) being established (e.g., [Si1], , [Si4], [Si5], , [Si6], ,, [Si7], [Si8], [Si9], [Si10], ,, and [Si12]). These various incompletely condensed silsesquioxanes may provide more possibilities to modulate the aggregation of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…In the next stage, further increase of phenanthroline loading allowed for the isolation of another intriguing example of CLMS, namely complex 5. In this case, one could identify a cyclic four-membered silsesquioxane ligand, earlier observed for various (Ti(IV)-, 79 Fe(III)-, 80 Co(II)-, 19 Zn(II)-, 25 Cu(II)-, 66 Ln(III)-, 24,32,81 and Mn(II)- 35 ) based CLMS complexes. Despite this, the structural type of 5 is unprecedented because complex 5 represents a cardinally different "open cage" molecular topology (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…[23][24][25] In the context of materials chemistry, we could also mention the applicability of CLMSs to designing anodes for fast sodium storage, 26 flame retardants [27][28][29][30][31] and polyfunctional (SMM/luminescent) objects. 32 Surprisingly scarce information is available about manganese-based silsesquioxanes. To the best of our knowledge, only a few examples of Mn 1 , Mn 2 , and Mn 3 -cubane structures, [33][34][35] Mn 4 and Mn 6 -sandwich-like complexes, 35,36 as well as high nuclear (Mn 8 Na 14 37 and Mn 10 Na 38 ) compounds have been previously reported (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of partly condensed POSS is also appealing, leading to the design of new monomers for copolymerization reactions, H-bond donor catalysts, OLED’s emission layers, three-dimensional emulsifiers, different films (e.g., transparent, scratch resistant, self-healing, or Langmuir–Blodgett/Langmuir–Schaefer films), and spin-on-glass networks with ultralow dielectric constants . By design, partly condensed polyhedral silsesquioxanes can be also regarded as versatile ligands for the construction of various cagelike metallacomplexes. These intriguing compounds attract significant interest for the potential removal of radioactive elements, fabrication of flame retardants, biomedical agents, luminescent materials, , or molecular magnets . Magnetic studies revealed rare cases of single-molecule magnets (SMMs), , spin glass, or spin–flip transition effects.…”
Section: Introductionmentioning
confidence: 99%
“…By design, partly condensed polyhedral silsesquioxanes can be also regarded as versatile ligands for the construction of various cagelike metallacomplexes. These intriguing compounds attract significant interest for the potential removal of radioactive elements, fabrication of flame retardants, biomedical agents, luminescent materials, , or molecular magnets . Magnetic studies revealed rare cases of single-molecule magnets (SMMs), , spin glass, or spin–flip transition effects. A wide number of metallasilsesquioxanes were also applied as efficient homo- or heterogeneous catalysts, , including activation of small molecules .…”
Section: Introductionmentioning
confidence: 99%